Candidate genes and gene expression analysis for response to salmonella enteritidis challenge in young Malaysia indigenous chickens - Tohidi, Reza (2012)
Salmonella enteritidis (SE) is a common cause of food-borne disease in humans and loss of growth in poultry. The main source of infection for humans is contaminated food especially poultry products. Protocol to control salmonellosis is similar that of other infectious diseases. However, resistance of the bacteria to antibiotics and non-effectiveness of vaccination have been reported. The effective method for inhibition of salmonellosis is increasing of genetic resistance of poultry to Salmonella through genetic selection programs that may be performed based on phenotypic or genotypic data. There are two major problems in the traditional selection for disease resistance. First, the heritability for resistance to salmonellosis is low and second, collection of data is generally not feasible, hazardous and impractical. Marker-assisted selection (MAS) has been introduced to improve these kinds of traits. For this goal, the choice of a suitable molecular marker or a candidate gene that being polymorphic for that is necessary. On the other hand, indigenous chickens have priority in selection programs for improving genetic resistance to disease, as these genetic types have been evolutionary adapted to the local environment. Based on these hypotheses, the objective of this study was to evaluate the ability to resist SE infection in Malaysian village and red jungle fowl chickens using candidate gene analysis. Three studies were designed for this goal. In the first study, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to investigate the levels of diversity in 16 candidate genes responsible for immunological reactions in chicken. These genes were inducible nitric oxide synthase (iNOS), natural resistance-associated macrophage protein 1 (NRAMP1), immunoglobulin light chain (IgL),transforming growth factor b family (TGFb2, TGFb3, TGFb4), interleukin 2 (IL2), inhibitor of apoptosis protein 1 (IAP1), toll like receptor (TLR4), myeloid differentiation protein 2 (MD2), interferon g (IFNg), caspase 1 (CASP1), lipopolysaccharide induced tumor necrosis factor (TNF)- factor (LITAF),tumor necrosis factor related apoptosis inducing ligand (TRAIL), cluster of differentiation 28 (CD28) and prosaposin (PSAP). Fourteen candidate genes were polymorphic and in Hardy-Weinberg equilibrium (HWE). The results of the current study showed that CD28 and PSAP were monomorphic in both breeds, and LITAF was monomorphic in the red jungle fowl. The minimum and maximum of the observed heterozygosity belonged to IL2 and TGFb4 in red jungle fowl, respectively. Allele ‘T’ of LITAF was fixed in red jungle fowl and allele ‘C’ of iNOS, ‘T’ of CASP1, ‘G’ of IL2 and ‘A’ of MD2 were present at low frequencies in red jungle fowl. Based on the Shannon information index (I),nine candidate genes were highly polymorphic in both breeds. However, iNOS and IL2 were highly polymorphic in only village chickens. In the second study, the association of different genotypes of 14 polymorphic candidate genes acquired from the first study with SE counts in the cecum,spleen and liver of the chickens was investigated. For this study, one day-old chicks were inoculated with 1 ´ 107 cfu/ml SE phage type 13a. The samples were collected seven days after inoculation. The bacterial counts in the cecum are more than in the spleen and liver (P < 0.01). Overall, the most significant associations were found for cecum and spleen SE counts. The polymorphisms in iNOS, NRAMP1, TGFb2, TGFb3, IL2, IFNg, TLR4 and TRAIL were associated with SE load. For liver, six genes (iNOS, TGFb2, TGFb3, TGFb4,TLR4 and TRAIL) had significant associations with SE counts. In the third study, the levels of expressions of five genes including NRAMP1,TLR4, IFNg, IgY and IL8 in cecum, spleen and liver 48 hours after inoculation with 1 ´ 107 SE in both breeds were analyzed. Real time reverse transcription PCR was used to quantify the fold change in mRNA expression. The results showed that all the genes were expressed highly 48 h after inoculation in the cecum of both breeds. However, IgY was significantly expressed in spleen. Moreover, the fold change in expression of IL8 was significantly higher in the liver of village chickens and red jungle fowl chicks (P < 0.05). The results of this study indicated that most of the candidate genes were highly polymorphic and only a few of them were monomorphic or lowly polymorphic. Random mating may be considered as the main reason for this high level of gene diversity. Moreover, some of these candidate genes (iNOS, NRAMP1, TGFb2, TGFb3, TGFb4, IL2, IFNg, TLR4 and TRAIL) were associated with SE burden in young chicks. Thus, they can be appropriate markers in selection programs. On the other hand, the immune genes were expressed after 48 h postinoculation in the cecum but not in spleen or liver. Therefore, the effects of immune genes should not be investigated for during the early hours after hatching to find suitable candidate genes in young chicks. Malaysian indigenous chickens have been adapted to the tropical environment and based on the result of this study, they can be considered as potential gene pool of alleles responsible for resistance to local diseases.